The SDGs in sustainability reports among companies in Ecuador, Colombia, and Chile - Retamal Ferrada, Lorena (2023)
The Sustainable Development Goals (SDGs) linked to the 2030 Agenda have been widely accepted by public and private companies, with many choosing to incorporate them within the framework of their social responsibility initiatives. This research article aims to find out how the SDGs are reflected in corporate sustainability reports and in which business activities they stand out the most. To this end, using a sequential explanatory methodology, the authors analyzed 12 sustainability reports issued in 2021 by large companies in Colombia, Chile, and Ecuador to verify their alignment with the SDGs. The reports showed evidence of a diverse range of programs associated with at least three SDGs, thus highlighting the importance of fulfilling not only the needs based on each company’s field of expertise but also those of its audiences and the community in general. The most prevalent SDGs were “decent work and economic growth” (SDG 8) and “gender equality” (SDG 5), followed by “responsible consumption and production” (SDG 12). This paper contributes to a growing interest among academia in the research on sustainability communication evidenced in annual reports.